Bernard Weinberg: A history of literary criticism in the italian renaissance. The University of Chicago Press, Chicago, Ill., 1961. Second impression 1963. Two vols., 1184 pp. 24 x 16 cm. - Nallim, Carlos Orlando (1966)
Fil: Nallim, Carlos Orlando. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras